Pathogenicity of Pythium species causing seed rot and damping-off in soybean under controlled conditions - Wei, Lai; Xue, Allen; Cober, Elroy; Babcock, Carolyn; Zhang, Jinxiu; Zhang, Shuzhen; Li, Wenbin; Wu, Junjiang; Liu, Lijun (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2010)
Pythium species cause seed rot (SR) and damping-off (DO) in soybean worldwide. In a previous study, a number of Pythium species were isolated from infected soybean plants across Ontario and Quebec, but their comparative pathogenicities to soybean were not examined. In the present research, 24 isolates from eight Pythium spp. were evaluated for their pathogenicity in causing soybean SR and DO in a greenhouse environment. The effect of temperature on the ability of these isolates to cause SR was also studied. There were significant differences among the eight Pythium spp. for both SR and DO. When tested at 25°C, Pythium ultimum was the most pathogenic species, causing 97.0% SR and 46.4% DO, on average, in the two soybean cultivars used. Pythium aphanidermatum was the second most pathogenic species, resulting in 88.5% SR and 41.8% DO. The two species resulted in significantly greater SR and DO than the other six species tested and were considered highly pathogenic. Of the two cultivars used in these trials, ‘Beechwood’ was significantly more susceptible than ‘Nattawa’ to both SR and DO. Temperature had a significant influence on SR caused by Pythium spp. At all four temperatures tested (4°C, 12°C, 20°C and 28°C), P. ultimum was highly pathogenic, while P. arrenomanes, P. coloratum and P. dissotocum were the least pathogenic. The interactions between temperature and Pythium spp. were more pronounced for P. aphanidermatum, which showed an increased percentage of SR with an increase in temperature, and for P. irregulare, P. macrosporum and P. sylvaticum, which showed a decreased percentage of SR with an increase in temperature.